Aksi Teror Dalam Perspektif Al-Qur’an: (Kajian Tematik Ibn Katsir Dalam Tafsirnya Al Qur’an Al Adzm) - Abdul Rouf (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2020)
This research is to describe and analyze Ibn Katsir's thoughts on terror in his tafsir book Al-Qur'an Al-'Adzim. The results of this study are expected to be used to add and deepen insights regarding terror in the perspective of the Al-Qur'an. This research is a library research with a qualitative approach. The material collected includes several theories, especially Ibn Katsir's commentary book